2021
DOI: 10.1016/j.atherosclerosis.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transgender hormonal treatment on high density lipoprotein cholesterol efflux capacity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…High plasma levels of estrogen in murine models have also shown to increase de novo lipid clearance of VLDL and LDL, increase synthesis of HDL and alter the expression of lipoprotein modifiers (Villa et al, 2012;Della Torre et al, 2016). In contrast, a study in macrophages taken from trans-women undergoing sex hormone therapy showed that the total HDL efflux decreased by 10.8% and ATP-binding cassette transporter A1 (ABCA1)-mediated HDL efflux by 23.8%; this hormone-driven effect may therefore be tissue specific (van Velzen et al, 2021). In addition, a study has reported that male patients with primary and secondary hypogonadism (low testosterone) presented with lower ABCA1/G1, suggesting an association with reduced cholesterol efflux (Adorni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…High plasma levels of estrogen in murine models have also shown to increase de novo lipid clearance of VLDL and LDL, increase synthesis of HDL and alter the expression of lipoprotein modifiers (Villa et al, 2012;Della Torre et al, 2016). In contrast, a study in macrophages taken from trans-women undergoing sex hormone therapy showed that the total HDL efflux decreased by 10.8% and ATP-binding cassette transporter A1 (ABCA1)-mediated HDL efflux by 23.8%; this hormone-driven effect may therefore be tissue specific (van Velzen et al, 2021). In addition, a study has reported that male patients with primary and secondary hypogonadism (low testosterone) presented with lower ABCA1/G1, suggesting an association with reduced cholesterol efflux (Adorni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HDL’s capacity to promote cholesterol efflux (CEC) through the main pathways was evaluated in patients’ HDL fraction by a standardized and widely used radioisotopic cell-based technique [ 53 ]. For HDL fraction isolation, the apoB-containing lipoproteins were precipitated from whole serum with a solution of polyethylene glycol [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of specific diseases, the HDL efflux 5):484-525, with permission from Elsevier) [47] capacity is negatively correlated with type 2 diabetes mellitus and to the incidence of CAD events, independent of other risk factors [65], although evidence of no association was reported in the CODAM Study in subjects with either elevated CVD risk or type 2 diabetes mellitus [66]. Conversely, CEC is impaired in individuals with familial hypercholesterolemia [67], systemic lupus erythematosus [68], nonalcoholic fatty liver disease [69], in women with polycystic ovary syndrome [70], or in individuals with hypogonadism or undergoing hormone affirming therapy [71][72][73]. In the context of CVD, the evaluation of HDL anti-inflammatory capacity is a functional metric, prospectively providing independent clinical information for the assessment of CVD, as in the case of Framingham Risk Score [74•].…”
Section: Hdl-the Functional Capacitymentioning
confidence: 99%